2004
DOI: 10.1016/j.orthres.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory fluid flow affects human marrow stromal cell proliferation and differentiation

Abstract: Mechanical loading is an important regulator of bone formation and bone loss. Decreased osteoblast number and function are important cellular mechanisms by which mechanical disuse leads to decreased bone formation. Decreased osteoblast number may be a result of decreased osteoprogenitor proliferation, differentiation, or both. However, the effects of cellular level physical signals on osteoprogenitors are not well understood. In this study, we examined the effects of loading induced oscillatory fluid flow (OFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(177 citation statements)
references
References 46 publications
9
166
1
1
Order By: Relevance
“…However, in this study no effect of OFF was demonstrated in the cell types examined. This result is similar to the study by Li et al (2004) who subjected MSCs to OFF in a parallel plate flow chamber and found the gene expression of collagen type I was not affected. Filipowska, Reilly, and Osyczka (2016) found that perfusion flow of hBMSC in porous polyurethane scaffolds could enhance osteogenic potential but had no effect on collagen production.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in this study no effect of OFF was demonstrated in the cell types examined. This result is similar to the study by Li et al (2004) who subjected MSCs to OFF in a parallel plate flow chamber and found the gene expression of collagen type I was not affected. Filipowska, Reilly, and Osyczka (2016) found that perfusion flow of hBMSC in porous polyurethane scaffolds could enhance osteogenic potential but had no effect on collagen production.…”
Section: Discussionsupporting
confidence: 91%
“…It was previously shown that OFF applied using similar conditions slightly upregulates ALP activity and collagen production and strongly upregulates calcium production in monolayer culture by hESMPs (Delaine‐Smith et al, 2012). Others also applied OFF to monolayer cultures of hBMSC or human fetal osteoblastic cells using a parallel plate flow chamber at a peak shear stresses of up to 2 Pa (Li et al, 2004). Fluid flow under an orbital shaker has also been shown to enhance chondrogenesis in HJPC (Ferretti & Mattioli‐Belmonte, 2014, Tarng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is often difficult to isolate the critical responding cell: for example, exposure to microgravity results in a decreased number of osteoblasts, but what cell senses and responds to the loss of gravity-the stromal cell, the differentiated osteoblast, or the distant, entombed osteocyte? Li et al found that marrow stromal cells change their proliferation rate and gene expression patterns in response to mechanical stimulation (Li et al, 2004). With respect to osteoclast number: stromal cell expression of the osteoclastogenic facto, RANKL is sensitive to mechanical force (Rubin et al, 1999(Rubin et al, , 2002c, suggesting that the number of osteoclasts present is controlled through mechanical regulation sensed by stromal cells.…”
Section: Mechanosensitive Bone Cellsmentioning
confidence: 99%
“…In essence, mechanical forces have been shown to activate every type of signal transduction cascade, from increases in intracellular cAMP (Lavandero et al, 1993), IP3 and intracellular calcium (Dassouli et al, 1993;Li et al, 2004), guanine regulatory proteins (Gudi et al, 2003), and MAPK (Rubin et al, 2002c). As previously stated, this review does not aim to collect each and every report of each signal cascade stimulated by mechanical force in bone cells.…”
Section: Mechanically Activated Intracellular Signaling Systemsmentioning
confidence: 99%
“…Our lab has previously shown that oscillatory fluid flow is a potent regulator of bone cell metabolism (2,21,30). A 2 hour exposure to oscillatory fluid flow was selected as the mechanical stimuli in this study based on a previous experiment where this exposure period was found to maximally impact the RANKL/OPG ratio (21).…”
Section: Oscillatory Fluid Flowmentioning
confidence: 99%